Turner & Hooch [videorecording (DVD)] - Spottiswoode, Roger; Hanks, Tom (Touchstone Home Video : Distributed by Buena Vista Home Entertainment, 2002)
A compulsively neat detective's tidy world goes to the dogs when he is forced to team up with a drooling slob of a junkyard dog named Hooch.